The Effects of Empowering Leadership, Job Crafting, and Well-Being on Job Performance - Sudibjo, Niko; Widiastuti, Astrid (Educational Management, 2021)
Teachers’ job performance is becoming an important thing that runs the school service to society. Teachers’ performance becomes the representatives of the school, direct or indirect. The study becomes more interesting when it involves empowering leadership and job crafting as the variables and well-being as the mediator. This study aims to find out the effect of empowering leadership, job crafting, and well-being towards XYZ school teachers' job performance. It used PLS-SEM as the method to calculate the data, and it involved 80 teachers. The data was collected by spreading an online questionnaire due to the pandemic Covid-19. As a result, there are positive relations between empowering leadership, job crafting, and well-being towards job performance. Keywords: empowering leadership, job crafting, well-being, job performance